Optimal pricing for a multi-echelon closed loop supply chain with different power structures and product dual differences. (1st June 2020) - Liu, Wenjie; Qin, Dingzhi; Shen, Ningning; Zhang, Jing; Jin, Mingzhou; Xie, Naiming; Chen, Jian; Chang, Xiangyun
Abstract: Main objectives of this research are to investigate the effect of different power structures and product dual differences, quality difference among used products and price difference between new ad remanufactured products, on pricing policies of a multi-echelon closed loop supply chain (MCLSC) and to propose future improvement strategies. To achieve these objectives, centralized and decentralized pricing models for the MCLSC were constructed to explore optimal member pricing and optimal profit under different power structures: centralized, Manufacturer-led Stackelberg ( MS ), Retailer-led Stackelberg ( RS ) and Collector-led Stackelberg ( CS ) pricing models and to analyze the impact of three key parameters, collection rate, cross-price elasticity coefficient, and quality grade ratio of used products. By comprehensive theory comparisons and a case study of auto alternators, the results of theoretic analysis indicated three insights. (1) The centralized pricing model always achieves the maximum total profit of the MCLSC, but the CS model obtained a minimum total profit. (2) For three decentralized pricing models, the optimal wholesale price and optimal retail price for new product and remanufactured product all increase with the collection rate and cross-price elasticity coefficient. For MS model and RS model, however, optimal acquisition price for used product decrease with the two parameters. (3) The optimal wholesale price and optimal retail price for new product rise up with the quality grade ratio in each decentralized pricing model. There are also three important findings from the case study. (1) When the collection rate is increased, the optimal total profit shows a U- shaped curve, with a profit trap around a certain collection rate. (2) The optimal acquisition price drops slightly with the cross-price elasticity coefficient, but the optimal wholesale price and optimal retail price increase sharply. This causes a benefit conflict between MCLSC members and consumers. It is recommended that the cross-price elasticity coefficient should be carefully controlled under a certain value to relieve the conflict. (3) When the quality grade ratio increases, optimal profits for all member and the system all increase and have a shell shape. They reach approximate maximum when remanufacturing ratio was raised to 95%. Major contributions of this paper are an effective decision tool for optimal pricing decisions of the MCLSC and insights for appropriate industrial policies and enterprise strategies to enhance the performance of the MCLSC. Highlights: ● Considerations on quality difference of used products and price difference of new and remanufactured products. ● A centralized pricing model and three decentralized Stackelberg pricing models for the multi-echelon closed-loop supply chain (MCLSC). ● Identification of the impacts of three key parameters (including collection rate, quality grade ratio and cross-price elasticity coefficient) on optimal pricing and profits. ● Industrial policies and business measures for governments and all members of MCLSC. ● A real-world case to validate the model and to provide managerial insights.